2018
DOI: 10.1039/c8ra02176g
|View full text |Cite
|
Sign up to set email alerts
|

On the synergy between silver nanoparticles and doxycycline towards the inhibition of Staphylococcus aureus growth

Abstract: Silver nanoparticles conjugated with doxycycline act synergistically to halt S. aureus growth via inhibition of protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Thus, the present results demonstrated that the prepared nanoantibiotic system could be potentially use in the treatment of antibiotic‐resistant bacteria. In another study by Silva et al., the changes in the metabolism of Staphylococcus aureus when exposed to Ag nanoparticles carrying Doxycycline were not simply additive effects of Doxycycline and silver nanoparticles separately but had synergistic effects, hindering bacterial protein synthesis [75] . Based on these experimental results, the incorporation of both antibiotics DOX, FLO, and AgNPs in a single nano‐drug delivery system expressed an excellent inhibitory effect on treating infectious diseases.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, the present results demonstrated that the prepared nanoantibiotic system could be potentially use in the treatment of antibiotic‐resistant bacteria. In another study by Silva et al., the changes in the metabolism of Staphylococcus aureus when exposed to Ag nanoparticles carrying Doxycycline were not simply additive effects of Doxycycline and silver nanoparticles separately but had synergistic effects, hindering bacterial protein synthesis [75] . Based on these experimental results, the incorporation of both antibiotics DOX, FLO, and AgNPs in a single nano‐drug delivery system expressed an excellent inhibitory effect on treating infectious diseases.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to exhibiting bactericidal and bacteriostatic properties [16,[30][31][32], silver nanoparticles (AgNPs) are known to present dose-and-time-dependent cytotoxicity in vitro and in vivo [33,34]. Herein, we set out to discovering the conditions under which the NC-AgNPs toxicity emerges.…”
Section: Cytotoxicity Of Nc-agnps Towards Hacat Cellsmentioning
confidence: 99%
“…Fluorescence spectroscopy has already been used in the detection 18 , structural investigation 19 , 20 and in the construction of a DNA biosensor for E. coli 21 . Chemometric methods such as Linear Discriminant Analysis (LDA) 22 , Quadratic Discriminant Analysis (QDA) 23 and Support Vector Machines (SVM) 24 , coupled with the dimensionality reduction algorithm: Principal Component Analysis (PCA) 25 , 26 ,and variable selection algorithms: Genetic Algorithm (GA) 27 and Successive Projections Algorithm (SPA) 28 , tend to enhance the spectroscopic techniques 29 31 .…”
Section: Introductionmentioning
confidence: 99%